Factors affecting tuberculosis cadres’ motivation in the detection of tuberculosis cases in Kediri City, Indonesia - Gita Sekar Prihanti; Eko Setyo Herwanto; Galih Bayu Prakoso; Gusti Gandha Pandya; Cha Cha Astrid Ghesa; Hiolda Lubvianda Oktavin; Yulanda Fitriana (Public Health and Preventive Medicine Archive, 2020)
Background and purpose: Tuberculosis (TB) is an infectiousdisease caused by Mycobacterium tuberculosis (MTB). The high incidence of TB acquires the active role of TB cadres in TB case finding. Motivation is an important factor that support the performance of TB cadres. This study aims to explore factors that affect the motivation of TB cadres case detection rate of TB. Methods: This was an observational analytic study with crosssectional study design, conducted in Kediri City. A total samplingtechnique was applied with a total of 59 TB cadres in the workingarea of Sukorame Public Health Center, in Kediri City. TB cadres filled in a questionnaire containing questions about sociodemographic, attitudes, knowledge, and motivation with a total of 39 questions. Data were analyzed with univariate descriptive statistics, bivariate test by Fisher and Chi Square tests and followed by multivariate analysis using logistic regression. Results: Of the 59 cadres, 37 (67.2%) have a good motivation onTB case findings. The results of multivariate analysis showed that there were four independent variables which have a significant association with the motivation of TB cadres, including age, education, jobs and incentive. Cadres who are 41-60 years have better motivation compared to 25-40 years (OR=31.49; 95%CI:2.373-417.907; p=0.009), cadres who have higher education (university/college) have better motivation (OR=36.957; 95%CI:2.389-571.805; p=0.010). While those who not getting incentives (OR=0.100; 95%CI: 0.013-0.758; p=0.026) and having a job (OR=0.120; 95%CI: 0.021-0.670; p=0.016) were less likely to have a good motivation. Conclusion: Motivation of TB cadres in Kediri City is influenced by intrinsic factors (age, education and employment) and extrinsic factor (incentive). Providing appropriate incentive will significantly boost cadre motivation and relevant stakeholders should consider making this strategy sustainable.